COVID-19 Case Data for Italy Stratified by Age Class. (26th April 2022) - Calafiore, Giuseppe; Fracastoro, Giulia
The dataset described in this paper contains daily data about COVID-19 cases that occurred in Italy over the period from Jan. 29, 2020 to October 15, 2021, divided into ten age classes of the population, the first class being 0–9 years, the tenth class being >90 years. The dataset contains eight columns, namely: date (day), age class, number of new cases, number of newly hospitalized patients, number of patients entering intensive care, number of deceased patients, number of recovered patients, number of active infected patients. This data has been officially released for research purposes by the Italian authority for COVID-19 epidemiologic surveillance ( Istituto Superiore di Sanità – ISS), upon formal request by the authors, in accordance with the Ordonnance of the Chief of the Civil Protection Department n. 691 dated Aug. 4, 2020. A separate file contains the numerosity of the population in each age class, according to the National Institute of Statistics ' (ISTAT) data of the resident population of Italy as of Jan. 2020. This data has potential use, for instance, in epidemiologic studies of the effects of the COVID-19 contagion in Italy, in mortality analysis by age class, and in the development and testing of dynamical models of the contagion.